The Home of the Cocoa-Nut [sic]. Trinidad - (:unkn) unknown (Muir, Marshall and Co., Port of Spain, Trinidad., 2009)
This postcard shows a single shed on the shore just in front of a forest of coconut trees. The postcard is addressed to Miss Shephard, Springfield, Miss., U.S.A. Affixed to the postcard is a Trinidad and Tobago 1 penny stamp, postmarked August 16, 1908.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coasts--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Sheds--Trinidad and Tobago; 1908